Development of negative ion source with combined discharge - Goretskii, V.P.; Dobrovolskiy, A.M. (Вопросы атомной науки и техники, 2015)
The results of investigation of emission productivity of negative particles source with combined discharge are presented. A cylindrical beam of negative hydrogen ions with density about 5 A/cm² on source emission aperture is obtained. The full beam current values are up to 200 mA for negative hydrogen ions and up to 1.5 A for electrons with high divergence after source. The source has simple design and produces stable discharge with low level of oscillation.